IFC Annual Report 2006 : Increasing Impact, Volume 2 - International Finance Corporation (Washington, DC, 2012)
The International Finance Corporation (IFC), in its 50th year, is the largest provider of multilateral financing for private sector projects in the developing world. In fiscal 2006, it committed $6.7 billion in funds from its own account and mobilized an additional $1.6 billion through syndications and $1.3 billion through structured finance. Based on the total costs of the private sector projects it helped finance this year, each $1 in IFC commitments for its own account resulted in an additional $2.88 in funding from other sources. Altogether, IFC supported 284 investment projects in 66 countries. This year nearly a quarter of IFC commitments were in low-income or high-risk countries, demonstrating the viability of private enterprise even in difficult environments. IFC's investment commitments to firms operating in the Middle East and North Africa more than doubled in fiscal 2006, and commitments for private sector projects in Sub-Saharan Africa increased nearly 60 percent. IFC introduced a new development outcome tracking system for investment operations to measure and track results throughout the life of a project; a similar system was implemented to monitor the development impact of all active technical assistance and advisory projects.